Being True to the Trans-: The Transglobal Science Fiction of Samuel R. Delany - José Liste-Noya (Journal of Transnational American Studies, 2018)
This essay begins with the recognition that science fiction, classic as well as contemporary, has always possessed a global, postnationalist imaginary, shying away from if also secretly conditioned by contemporary nationalist and imperialist scenarios. In recent critical work on SF, critics such as Fredric Jameson have persuasively argued that contemporary SF is a privileged literary mode of “cognitive mapping” of the inherently unrepresentable, technologically conditioned global economy. Samuel R. Delany’s 1984 novel, Stars in My Pockets Like Grains of Sand, dramatizes such an insight via a literally “transglobal” extrapolation of our current transnational dynamics. In the process, I suggest, the transglobal fictional world of Delany’s novel counters totalizing notions of the global and of the literal globe which is a planetary world by exposing the “plural singularity” of any and all worlds. Drawn from the work of Jean-Luc Nancy, the phrase points to the novel’s and the essay’s exploration of the juxtaposition between the notion of world and the global in order to pinpoint the paradoxical tendencies of globalization, its simultaneous opening up of the singular differences of world(s) and its homogenizing curtailment of such diversity within the enclosure of globality. Delany’s tale of desire, sexual and political, becomes a demonstration of science fiction’s straining at the boundaries of the global by tracing the postnational utopian impulse inherent to the very idea of the transnational.